Identification of Alkaloids from Terminalia chebula as Potent SARS‐ CoV‐2 Main Protease Inhibitors: An In Silico Perspective. Issue 14 (11th April 2022) - Ghosh, Rajesh; Badavath, Vishnu Nayak; Chowdhuri, Snehasis; Sen, Anik
Abstract: Natural compounds in medicinal plants are best remedies for different diseases and are important to develop new drugs. This work was dedicated to understand the role of different natural compounds of Terminalia Chebula, a well‐known herbal plant, in the treating of Covid 19. In this article, we have investigated interactions of such natural compounds from Terminalia Chebula with the main protease (M pro ) of the SARS‐CoV‐2, which is a key component for cleavage of viral polyprotein, and an important target for the development of drugs towards COVID‐19. We have performed molecular docking study on 22 different molecules of Terminalia Chebula and proposed that 7 of the natural compounds (triterpenoids and sterols) interacts with a comparable or stronger interactions than the inhibitor N3. Molecular dynamics simulations (100 ns) revealed that 7 M pro ‐ Terminalia Chebula complexes are stable, conformationally less fluctuated, slightly less compact, and marginally expanded than ligand‐free conformation of M pro . The intermolecular H‐bonding and detailed MM/PBSA and MM‐GBSA analysis showed Daucosterol interaction to be the most strong, whereas comparable interactions were observed for Arjunetin, Maslinic acid, and Bellericoside. Our study suggested that these natural compounds can act as potent M pro inhibitors for SARS‐CoV‐2, and may evolve as promising anti‐COVID‐19 drugs in the near future. Abstract : A detailed in silico studies have been performed on the natural compounds of the Terminalia Chebula, a well‐known herbal plant as potential targets against M pro of SARS‐CoV‐2, through docking and Molecular Dynamics simulations. Our results showed Daucosterol, Arjunetin, Maslinic acid, and Bellericoside may evolve as promising anti‐COVID‐19 drugs in the near future.